2011
DOI: 10.3892/ijmm.2011.818
|View full text |Cite
|
Sign up to set email alerts
|

Losartan inhibits conventional dendritic cell maturation and Th1 and Th17 polarization responses: Νovel mechanisms of preventive effects on lipopolysaccharide-induced acute lung injury

Abstract: Abstract. Acute lung injury (ALI) remains one of major causes of morbidity and mortality in intensive care medicine. The lack of efficient pharmacological interventions contributes to the high mortality rate of ALI. Losartan, an antagonist of angiotensin II (Ang II) type 1 receptor, is a potent therapeutic drug for ALI. Recent reports suggest that losartan inhibits the maturation of dendritic cells (DCs), impairs T-helper (Th) 1 immune response and ultimately attenuates inflammation in several Ang II-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…Our group and others have shown that Ang II plays a pivotal role in regulating the T cell response in an autocrine or paracrine manner via AT 1 R, which is upregulated in activated T cells10111213141521. In addition, other studies show that different innate immune cells, such as monocytes, macrophages, and dendritic cells, produce Ang II and express higher levels of mRNA of the different renin-angiotensin system (RAS) components than T cells8101617181920. During the encounter with the antigen, in the context of co-stimulatory stimuli, Ang II activates AT 1 R in T cells initiating distinct transcriptional profiles that regulate avidity by antigen, activation, clonal expansion, migration and effector function101112131415161718192021.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Our group and others have shown that Ang II plays a pivotal role in regulating the T cell response in an autocrine or paracrine manner via AT 1 R, which is upregulated in activated T cells10111213141521. In addition, other studies show that different innate immune cells, such as monocytes, macrophages, and dendritic cells, produce Ang II and express higher levels of mRNA of the different renin-angiotensin system (RAS) components than T cells8101617181920. During the encounter with the antigen, in the context of co-stimulatory stimuli, Ang II activates AT 1 R in T cells initiating distinct transcriptional profiles that regulate avidity by antigen, activation, clonal expansion, migration and effector function101112131415161718192021.…”
Section: Discussionmentioning
confidence: 98%
“…Although Ang II binds 2 different receptors, AT 1 R and AT 2 R, previous studies have shown that AT 1 R expression is upregulated in T cells in vitro and during Plasmodium berghei ANKA (PbA) infection and mediates most of the effects of Ang II in T cells56789101112131415182021. The upregulated AT 1 R plays a role in activation, effector function, CD8 + T-cell sequestration in the brain, cerebral edema, and behavioral impairment during the blood stage of PbA infection, as well as in other models of diseases1011131518192021. However, the specific role of AT 1 R expressed by antigen-specific CD8 + T cells in regulating their response is not yet clear yet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations